Exploring the interplay of sensory hypersensitivity and autistic traits in children - Shima keshavarz; Khalil Esmaeilpour (BMC Psychology)
Abstract Objectives Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by social challenges and repetitive behaviors, influenced by genetic and environmental factors. Autistic traits, including variations in sensory processing, exist across both clinical and subclinical spectrums, impacting individuals with and without an ASD diagnosis. Given the importance of understanding sensory processing in individuals with autism, this essay aims to explore the relationship between autistic traits and sensory hypersensitivity within the general population. Materials & methods This cross-sectional study, was based on caregiver reports of 247 children aged 7 to 11 years. The parents completed the Autism-spectrum Quotient-Children’s Version (AQ-C) and the Short Sensory Profile 2 (SSP2). using the multiple regression analysis, we investigated the relative contributions of different AQ sub-scales to sensory hypersensitivity scores. A one-way analysis of variance (ANOVA) was then conducted to determine whether sensory hypersensitivity levels (categorized as typical performance, probable difference, and definite difference) influenced overall autistic traits. Additionally, Spearman’s rank-order correlations were used alongside parametric tests to explore the relationships between sensory hypersensitivity subgroups (Tactile Sensitivity, Taste/Smell Sensitivity, Movement Sensitivity, Seeks Sensation, Auditory Filtering, Low Energy, and Visual/Auditory Sensitivity) and AQ scores. Results while Pearson correlation analysis revealed a significant linear relationship between AQ scores and the total sensory score (r = -.496**, p <.01), The multiple regression model revealed that, among autistic traits, only Attention Switching (β = − 0.291, p =.000) and Communication (β = − 0.479, p =.000) were significant predictors of hypersensitivity. Furthermore, the result of one-way ANOVA indicated a significant effect of sensory hypersensitivity sub-scales on autistic traits, F (2, 241) = 33.096, p <.01. Conclusions Based on the results, a link between sensory processing and autistic traits in the general population was confirmed. These insights underscore the importance of considering sensory processing differences when assessing autism-related traits and could inform targeted interventions for individuals experiencing sensory challenges.